Moray micro forceps biopsy improves the diagnosis of specific pancreatic cysts. Issue 6 (16th April 2018) - Zhang, M. Lisa; Arpin, Ronald N.; Brugge, William R.; Forcione, David G.; Basar, Omer; Pitman, Martha B.
Abstract : BACKGROUND: Making a specific diagnosis of pancreatic cysts preoperatively is difficult. The new disposable Moray micro forceps biopsy (MFB) device allows tissue sampling from the pancreatic cyst wall/septum and aims to improve diagnosis. This study compares the diagnostic performance of the MFB with the current conventional analysis of pancreatic cyst fluid (PCF). METHODS: A total of 48 patients sampled with MFB were identified. Cysts were classified as mucinous on PCF based on extracellular mucin/mucinous epithelium, carcinoembryonic antigen (CEA) levels ≥192 ng/mL, or KRAS/GNAS mutation. A diagnosis of intraductal papillary mucinous neoplasm was supported by GNAS mutation; a diagnosis of serous cystadenoma was supported by Von Hippel‐Lindau tumor suppressor ( VHL ) mutation. A diagnosis of mucinous cystic neoplasm required the presence of subepithelial ovarian‐type stroma. A high‐risk cyst was defined as a mucinous cyst with high‐grade dysplasia or an adenocarcinoma. Comparisons in diagnostic performance between PCF and MFB were made. RESULTS: The mean age of the patients was 69.6 years (range, 27‐90 years); 25 of 48 patients (52.1%) were female. Cysts were in the pancreatic head (13 patients), neck (2 patients), body (20 patients), and tail (13 patients), averaging 3.1 cm (range, 1.2‐6.0 cm). There was concordance with mucinous versus nonmucinous classification (60.4% for PCF vs 58.3% for MFB; P = .949). Three high‐risk cysts were detected by PCF and 2 were detected by MFB ( P = .670). However, MFB diagnosed significantly more specific cysts compared with PCF (50.0% for MFB vs 18.8% for PCF; P <.001). CONCLUSIONS: PCF analysis and MFB have comparable performance in distinguishing between mucinous and nonmucinous cysts and for detecting high‐risk cysts. However, MFB was found to be superior for diagnosing specific cyst subtypes, thus adding significant value to preoperative patient management. Cancer Cytopathol 2018;126:414‐20. © 2018 American Cancer Society . Abstract : There is high variability in cytological expertise and the ability to analyze pancreatic cyst fluid, and the preoperative diagnosis of pancreatic cysts remains challenging. The new Moray micro forceps biopsy device can procure tissue for histologic evaluation during endoscopic ultrasound‐guided fine‐needle aspiration and facilitates the preoperative diagnosis of significantly more specific pancreatic cyst subtypes.